A grammar of Jingulu : an Aboriginal language of the Northern Territory - Pensalfini, Robert J.; Australian National University. Research School of Pacific and Asian Studies. Pacific Linguistics (Canberra : Pacific linguistics, Research School of Pacific and Asian Studies, Australian National University, 2003)
Overview of the Jingulu language, the traditional language of the Jingili people; kinship and sub section system; phonology; parts of speech and derivation; syntax; nominal morphology; the verb complex; sample texts.
Bibliography.
Keywords: Djingili language -- Grammar; Australian languages -- Northern Territory -- Grammar; Australian languages -- Northern Territory; Djingili language; Language - Texts and translations - Aboriginal to non-Aboriginal language; Social organisation - Kinship - Kinship terms; Jingulu / Djingili / Jingili language (C22) (NT SE53-06); Language - Linguistics - Grammar and syntax; Language - Linguistics - Vocabulary and grammar; Language - Linguistics - Grammar and syntax - Parts of speech; Jingulu / Djingili / Jingili people (C22) (NT SE53-06); Elliott / Gurungu (North NT SE53-06)